Alexander Evgenievich Loskutov - Association of Orthopedic Traumatologists of Ukraine (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
May 26, 2025 marks the 75th anniversary of the birth and 52 years of medical, scientific, pedagogical and public activity of the Head of the Department of Traumatology and Orthopedics of the Dnipro State Medical University, Academician of the National Academy of Medical Sciences of Ukraine, Doctor of Medical Sciences, Professor, Honored Worker of Science and Technology of Ukraine, laureate of the State Prize of Ukraine Oleksandr Yevgeniyovych Loskutov.